STUDI KESULITAN BELAJAR MAHASISWA JURUSAN PENDIDIKAN IPA DALAM MEMPELAJARI SIFAT PERIODIK UNSUR - Sari, Monica Prima; Andromeda, Andromeda; Hardinata, Aristo (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Periodical properties of elements are not a new topic for students in science education department for they have studied this topic previously in senior high school and in General Chemistry course. However, teaching experiences for the past two years in Basic Inorganic Chemistry course revealed that many students still failed to master the expected learning outcomes for this topic. Therefore, this explorative study was conducted to figure out what kind of difficulty that students perceived in learning this topic. One hundred and twelve students in science education department of Universitas Negeri Padang enrolled in Basic Inorganic Chemistry course in the academic year of 2017/2018 were involved as subjects in this study, and data of students? perceived learning difficulties were collected with a questionnaire. Data were analyzed with descriptive statistics technique to map out our findings which will become the fundamental consideration in discussing attempts to overcome students? perceived learning difficulties. Our findings revealed that the sources of students? perceived difficulty came from several factors, namely: the characteristic of content, personal learning style, condition of classroom learning, availability of relevant learning resources and previous learning experiences. Based on these findings, attempts for better learning of periodical properties of elements were suggested.